NEW PROCEDURE FOR ESTIMATION OF THE PHYSICAL VALUES - T.V., Barashkova; V.А.Shirokova (IJRDO-Journal of Applied Science, 2018)
This paper compares the methods of checking the state of rolling bearing for high-frequency vibration. For more accurate registration of impact loads at low shaft speeds a program was created that allows recording the impact load every millisecond. Multifractal analysis application possibilities in materials properties investigation are considered in the given article. Theory of multifractal analysis being considered in this work can be used as a new procedure for estimation of materials corrosion degree. The technology of calculations given in this work is directed to practical determination of scaling parameter a with the help of Scilab software. Fractal theory provides an effective method to describe the complexity and irregularity of the vibration signals of rolling bearings. In this paper considered formalism of geometric description of multifractal.